2006
DOI: 10.1038/sj.bjc.6603286
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic, blood vessel and perineural invasion identifies early-stage high-risk radically resected gastric cancer patients

Abstract: The availability of different treatment options for radically resectable gastric cancer reopened the question of treatment selection and correct definition of high-risk categories. Lymphatic, blood vessel and perineural invasion (LBVI/PNI) seem to possess the necessary potential to provide useful information for the clinical management of this disease. Seven hundred and thirty-four patients with advanced gastric cancer who underwent curative gastrectomy were analysed according to the presence of LBVI/PNI. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
33
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 20 publications
3
33
0
2
Order By: Relevance
“…Our findings are in concordance with the results of other investigators who have shown that in resected gastric and esophageal cancer, lymphovascular, or PNI is associated with poor survival. 30,31,32 In particular, Scartozzi et al 32 reported that in resected early stage, gastric cancer, lymphovascular or PNI predicts for OS and disease-free survival. In our study, we demonstrate the added benefit of PNI in discriminating survival in patients with advanced stage gastric cancer after preoperative chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in concordance with the results of other investigators who have shown that in resected gastric and esophageal cancer, lymphovascular, or PNI is associated with poor survival. 30,31,32 In particular, Scartozzi et al 32 reported that in resected early stage, gastric cancer, lymphovascular or PNI predicts for OS and disease-free survival. In our study, we demonstrate the added benefit of PNI in discriminating survival in patients with advanced stage gastric cancer after preoperative chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Why carcinomas exhibit a predilection for perineural invasion and others do not remains unknown. Perineural invasion is emerging as an important feature in many malignancies, including oropharyngeal, 12 prostate, 13 colorectal, 14 biliary, 15 gastric, 16 lung, 17 breast, 18 and ampullary cancers. 11 The highest rate of perineural invasion is documented in pancreatic cancer, head and neck squamous cell carcinomas, and prostate cancer, while lower rates are documented in gastrointestinal cancers.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18] While perineural invasion has been evaluated as a prognostic factor in patients with periampullary malignancies including pancreatic adenocarcinoma, distal cholangiocarcinoma, and ampulla of Vater carcinoma, 8,11,19 we know of no studies which have addressed the significance of perineural invasion in a large series of patients with duodenal adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…However, PNI is found to be related to a more aggressive tumor phenotype and poor prognosis in several malignancies, most notably head and neck and prostate cancers [2,3]. The prognostic importance of PNI in gastric cancer (GC) had been evaluated in a few studies, but they had not reached consensus [4,5]. Recently, Bilici et al [6] indicated that the incidence of PNI in GC was higher, and it was related to the progression of patients with GC.…”
Section: Introductionmentioning
confidence: 96%